(untitled) (Superficies y Vacío, 2019)
The use of microwaves for the synthesis of materials is very important due to its versatility, it is an economical option, friendly with the environment, generates a low energy demand and the syntheses are carried out in very short times. There are many methods that use microwaves to obtain materials, however, the simplest one is the ceramic method, which consists in blending by grinding the reagents or precursors, which are placed in a quartz cell and finally carried to the microwave oven for synthesis. The reagents used to carry out this research are ?-Bi2O3 and graphite. The phase change in the ?-Bi2O3 was obtained despite the differences in weight composition and the variation of power level and irradiation time inside the microwave oven. X-ray diffraction and scanning electron microscopy were used to verify the phase and morphology of the samples before and after irradiation. The last step of this work was the capacitance measurement of the composites made of 0.39 g of alumina and 0.01 g of the product of graphite and bismuth oxide after irradiation at different conditions. The results demonstrated an increasing of capacitance in all the samples conformed by ?-Bi2O3/C/Al2O3.